The effect of right versus left long-term single-sided deafness on sound source localization - Qingqing Xia; Shuoshuo Kang; Qian Wang; Mengdi Hong; Aiting Chen; Wei Chen; Fei Ji; Jianan Li; Shiming Yang (Journal of Otology)
Purpose: To analyze the effect of right versus left long-term single-sided deafness (SSD) on sound source localization (SSL), discuss the necessity of intervention and treatment for SSD patients, and analyze the therapeutic effect of long-term unilateral cochlear implantation (UCI) from the perspective of SSL. Methods: This study included 25 patients with SSD, 11 patients with UCI, and 30 participants with normal hearing (NH). Their SSL ability was tested by obtaining their average root mean square (RMS) error values of SSL test. Results: The results showed that the RMS error value of SSD, UCI and NH groups were 52.26 ± 20.25°, 69.84 ± 12.14° and 4.27 ± 2.66°, respectively. The ability of SSL was better in the SSD-L group than that in the SSD-R group, and no significant difference existed in the SSD-R and the UCI group. Conclusion: When bilateral deafness patients select unilateral treatment, right-side cochlear implantation may be more beneficial in terms of SSL, which means that the central auditory cortex in long-term SSD patients is affected differently based on which side their deafness occurs.